Cluster analysis - Uprichard, Emma.; Byrne, D. S. (David S.), 1947-; Sage eBooks (Los Angeles ; London : SAGE, 2012)
This collection considers issues of classification, cluster analysis and data mining together, presenting a range of existing work together in an accessible way, and demonstrating a methodological phase-shift in the kind of data analysis that is currently taking place, nationally and internationally.
Specialized.
Description based on print version record.
Includes bibliographical references.
Keywords: Social sciences -- Statistical methods; Cluster analysis; Electronic books